The Relation of Community Knowledge and Attitude by The Application of Management in Producing The Good Quality (ASUH) of Meat Chicken in Bali - Y. N. S., Dorothy; Inggriati, N. W. T.; Miwada, I N. S. (Jurnal Peternakan Tropika, 2018)
Research objectives were to know knowledge level and attidue of slaughtering chicken entrepreneur in the application of producing safe, healthy, fixed and “halal” meat in Bali. This study was conducted in two district, namely: city of Denpasar (UD. Budijaya), district of Tabanan (UD. Rasmin Indah and PT. Ciomas Adi Satwa), which lasts 3 months, start from May until July 2018. Selection of research locations using Purposive Sampling method and the determination of respondents was taken by census. Respondents from this study amounted 30 person, owners and the labour of chicken slaughterhouse (RPA). The data used in this study is the primary data and secondary data. The primary data obtain form the direct interview and observation while secondary data obtained from note in the Animal Husbandry and Animal Health Service of Bali province. The analysis used is qualitative descriptive analysis and spearmen level correlation test. The results of this study indicate that the level of knowledge is a high and attitudes are very positive while the application is excellent. Factors related to the application of chicken entrepreneurs as like as age has unreal relationship (p>0,10), the level of education has unreal relationship (p>0,10) with implementation with chicken entrepreneurs in Bali and the level of knowledge has a real relationship (p<0,10) with implementation of chicken entrepreneurs in Bali, as well as on the attidue of having a real relationship (p<0,10). The conclusion of this study shows that the level of knowledge is in the high category, attitudes are categorized as very positive, the application is in the very good category, and the level of knowledge and attitudes are significantly positive with the application of chicken slaughter management in producing ASUH chicken meat in Bali.   Keywords: chicken slaughterhouse (RPA), the application of management.